Alternativa Zero : Tendencias Polémicas na Arte Portuguesa Contemporãnea Lisboa 1977. - Prado Coelho, Eduardo; de Sousa, Ernesto (Lisboa: Galeria Nacional de Arte Moderna Belém, 1977)
Capdeville, Constança ; Alvess ; de Sousa, Angelo ; Castro, Melo E ; Andrade, Pedro ; Varela, Mário ; Vieira, Pires ; Costa, Noronha Da ; Almeida, Helena ; Carneiro, Alberto ; Hatherly, Ana ; Gentil-Homem, Carlos ; Rocha, Da ; Lapa, Alvaro ; Rodrigues, José ; Rosa, Joana Almeida ; Belem, Vitor ; Vieira, Ana ; Moura, Leonel ; Peixinho, Jorge ; Pomar, Vitor ; Bragança, Julio ; de Sousa, Ernesto ; Azevedo, Armando ; Sarmento, Julião ; Tavares, Salette ; Sena, Antonio ; Pinheiro, Jorge ; De Varela, Artur ; Silva, Sena Da ; Meneres, Clara ; Perreira, Lisa Chaves ; Casimiro, Manuel ; Vieira, Joào ; Calhau, Fernando ; Pereira Coutinho, Graça ; Saldanha, Tulia ; Brehm, Joao ; Alves, José Manuel Costa
biografie
Portugees & Engels
kunstcatalogus
Keywords: Portugal